Unemployment and indeterminacy - Tomoyuki Nakajima (Brown University, Department of Economics, 2003)
Using an efficiency-wage model, we examine the relationship between indeterminacy and unemployment insurance. It is shown that the less unemployment insurance is, the more likely equilibrium is to be indeterminate. Equilibrium can be indeterminate even without externalities or increasing returns, which makes a sharp contrast to the recent literature on indeterminacy. Our result is based on the fact that the no-shirking condition with marginal utility ofw ealth kept constant is downward sloping when income insurance is not perfect.
Keywords: E10; E24; E32; J41; 330; involuntary unemployment; efficiency wage; indeterminacy; sunspots; Effizienzlohn; Arbeitslosenversicherung; Sunspot; Theorie; Unfreiwillige Arbeitslosigkeit; Gleichgewicht